(untitled) (Revista "Boletín el Conuco", 2022)
The implied volatility in the markets has generated fluctuations that put companies, economies and consumers at risk. Therefore, to avoid these risks from causing an impact on food safety or even on the financial policy of a country; byproduct instruments are created to ensure the benefits in the productive activity of those who are directly related to basic products. This study looks for analyzing the risk in the rice sector and comprehends that the different byproduct instruments are tools that allow mitigating all types of risk in order to ensure the benefits of this sector, considered risky by investors and financial entities.